LEGAL REVIEW OF ADDITIONAL CRIMINAL SANCTIONS IN DECISION NUMBER 17/PID.SUS-TPK/2023/PN PLK - Theresia; Rico Septian Noor; Rizki Setyobowo Sangalang (RADJA PUBLIKA, 2026)
Decision Number 17/Pid.Sus-TPK/2023/PN Plk, handed down by the Palangka Raya Corruption Court against defendants Ben Brahim S. Bahat, former Regent of Kapuas, and Ary Egahni, member of the Indonesian House of Representatives, is an example of the application of additional penalties in corruption cases. The judge not only imposed the principal penalty of imprisonment and a fine, but also additional penalties in the form of a replacement payment of Rp8.8 billion and revocation of political rights to be elected to public office for five years after completing the sentence. This study aims to analyze the judge's considerations in imposing these additional penalties using normative, philosophical, and sociological approaches, and in relation to applicable criminal theories in Indonesia. The results of the analysis indicate that the additional penalty of replacement money was imposed based on Article 18 of the Corruption Law and Supreme Court Regulation Number 5 of 2014, with the consideration of returning state losses proportionally. Meanwhile, the revocation of political rights is based on Article 35 of the Criminal Code and the Constitutional Court Decision which confirms the constitutionality of the revocation of political rights of corruption perpetrators. From a sentencing theory perspective, the judge balanced the objectives of retributive, deterrence, and corrective justice. This decision demonstrates that the court not only upholds the law but also safeguards the integrity of democracy and rebuilds public trust in anti-corruption efforts.